Measuring sustainable employability: psychometric properties of the capability set for work questionnaire - Sait Gürbüz; Margot C. W. Joosen; Dorien T. A. M. Kooij; Arnold B. Bakker; Jac J. L. van der Klink; Evelien P. M. Brouwers (BMC Public Health, 2022)
Abstract Background The capability set for work questionnaire (CSWQ) is being used to measure the new model of sustainable employability building on the capability approach. However, previous studies on the psychometric properties of the instrument are limited and cross-sectional. This two-way study aimed to (1) evaluate the convergent validity of the CSWQ with the theoretically related constructs person-job fit, strengths use, and opportunity to craft and (2) test the predictive and incremental validity of the questionnaire for the well-established work outcomes, including work ability, work engagement, job satisfaction, and task performance. Methods A representative sample of 303 Dutch workers, chosen with probably random sampling, were surveyed using a one-month follow-up, cross-lagged design via the Longitudinal Internet Studies for the Social Sciences panel. The convergent validity was assessed by exploring the strength of associations between the capability set for work questionnaire and the theoretically related constructs using Pearson’s correlations. The predictive and incremental validity was evaluated by performing a series of linear hierarchical regression analyses. Results We found evidence of the convergent validity of the capability set score by moderate correlations with person-job fit, strengths use, and opportunity to craft (r = 0.51–0.52). A series of multiple regression analyses showed that Time 1 capability set score and its constituents (i.e., importance, ability, and enablement) generally had predictive and incremental validity for work ability, work engagement, job satisfaction, and task performance measured at Time 2. However, the incremental power of the CSWQ over and above conceptually related constructs was modest. Conclusions The findings support the convergent, predictive, and incremental validity of the capability set for work questionnaire with not previously investigated work constructs. This provided further evidence to support its utility for assessing a worker’s sustainable employability for future research and practical interventions.